Impact of Haemodialysis on Insulin Kinetics of Acute Kidney Injury Patients in Critical Care - Ummu Kulthum, Jamaludin; Docherty, Paul D.; Chase, J. Geoffrey; Shaw, Geoffrey M. (Springer, 2015)
Critically ill patients are occasionally associated with an abrupt decline in renal function secondary to their primary diagnosis. The effect and impact of haemodialysis (HD) on insulin kinetics and endogenous insulin secretion in critically ill patients remains unclear. This study investigates the insulin kinetics of patients with severe acute kidney injury (AKI) who required HD treatment and glycaemic control (GC). Evidence shows that tight GC benefits the onset and progression of renal involvement in precocious phases of diabetic nephropathy for type 2 diabetes. The main objective of GC is to reduce hyperglycaemia while determining insulin sensitivity. Insulin sensitivity (S I ) is defined as the body response to the effects of insulin by lowering blood glucose levels. Particularly, this study used S I to track changes in insulin levels during HD therapy. Model-based insulin sensitivity profiles were identified for 51 critically ill patients with severe AKI on specialized relative insulin nutrition titration GC during intervals on HD (OFF/ON) and after HD (ON/OFF). The metabolic effects of HD were observed through changes in S I over the ON/OFF and OFF/ON transitions. Changes in model-based S I at the OFF/ON and ON/OFF transitions indicate changes in endogenous insulin secretion and/or changes in effective insulin clearance. Patients exhibited a median reduction of −29 % (interquartile range (IQR): [−58, 6 %], p = 0.02) in measured S I after the OFF/ON dialysis transition, and a median increase of +9 % (IQR −15 to 28 %, p = 0.7) after the ON/OFF transition. Almost 90 % of patients exhibited decreased S I at the OFF/ON transition, and 55 % exhibited increased S I at the ON/OFF transition. Results indicate that HD commencement has a significant effect on insulin pharmacokinetics at a cohort and per-patient level. These changes in metabolic behaviour are most likely caused by changes in insulin clearance or/and endogenous insulin secretion.